COMPARATIVE REVIEW OF VARIOUS ORGANIC WASTES DERIVED FROM ANIMALS AND PLANTS IN ANAEROBIC DIGESTION FOR BIOGAS PRODUCTION - Helena - Febrianti; Fajar Pendawa; Muhammad Rivaldo Hanitama; Rusdianasari Rusdianasari (Universitas Mercu Buana, 2026)
Abstract–Increased production of organic waste from the livestock, agriculture, urban, and agro-industrial sectors poses significant environmental challenges if not managed properly. Anaerobic digestion (AD) is an effective technology for processing organic waste while producing renewable energy in the form of biogas. However, the performance of the AD process is greatly influenced by substrate characteristics, such as the carbon to nitrogen (C/N) ratio, lignocellulose content, nitrogen content, and chemical conditions of the substrate. This article aims to conduct a comparative review of various types of animal and plant-based organic waste used in biogas production through the AD process, with an emphasis on methane potential, operational constraints, and process optimization strategies. The method used is a narrative literature review of national and international journal articles discussing the utilization of livestock manure (cattle, chicken, pigs, and goats), food waste, lignocellulosic biomass (rice straw, water hyacinth, and grass), and agro-industrial liquid waste (tofu liquid waste and Palm Oil Mill Effluent/POME). The results of the study show that cow manure has good process stability but relatively moderate methane yield, while chicken and pig manure have higher methane potential but are susceptible to ammonia inhibition. Plant-based and agro-industrial waste generally has high energy potential, but faces obstacles in the form of slow hydrolysis, acidic pH, and nutrient imbalance. Based on the results of the study, anaerobic co-digestion (ACoD) has been proven to be the most effective strategy for optimizing biogas production. This approach is able to balance the C/N ratio, increase buffer capacity, reduce inhibition effects, and improve microbiological stability. The combination of substrates that produces a mixed C/N ratio in the optimal range of 20–30 has been consistently reported to increase methane yield and AD process stability. Thus, substrate selection and formulation through co-digestion are key to developing an efficient and sustainable biogas system.